Beckman Model 958 NOx efficienty tester
This instrument measures the nitrogen oxides (NOx) produced during the combustion of gasoline. Once in the atmosphere, they can contribute to the formation of smog and air pollution. Beckman Instruments, Inc. became interested in measuring, controlling, and fighting air pollution in the late 1940s and early 1950s, when company president Arnold O. Beckman became the scientific adviser to the Los Angeles Chamber of Commerce’s Air Pollution Control Officer. Many of the instruments that were developed by Beckman Instruments in the 1940s and 1950s as standalone items became incorporated into or re-purposed as smog-fighting systems.
Keywords: Scientific apparatus and instruments; Motor vehicles--Pollution control devices; Automobiles--Motors--Exhaust gas--Measurement; Beckman Instruments, Inc.